E-government challenges in developing countries: development of Iraqi E-government / Ahmed Totonchi and Abd Rahman Ahlan - Totonchi, Ahmed; Ahlan, Abd Rahman (UiTM Cawangan Perlis, 2023)
E-government involves utilizing technology to provide information and deliver governmental services to employees, citizens, and businesses. Developing countries implementing e-government should aim to keep pace with rapid technological advances to continuously improve their systems and enhance the services offered to citizens through government portals in an efficient manner requiring minimal time and effort. However, many developing nations, especially many Arabic countries, face numerous challenges in implementing and adopting e-government initiatives. This paper examines the concept, sectors, and definition of e-government, along with the potential benefits. It then discusses the current status of egovernment in Iraq, focusing on the issues and obstacles impacting the further development of egovernment systems in the country. The goal is to provide an overview of e-government and its applications while analysing the specific difficulties Iraq faces in advancing its e-government efforts to identify strategies to overcome these barriers